Montaje de banco de pruebas eléctricas para el taller de mantenimiento de la zona industrial del campo Tibú, Norte de Santander - López Rivera, Diego Andrés (Universidad Antonio Nariño, 2022)
The main objective of the project is to carry out the implementation of the workbench and tests for the electrical workshop of the maintenance area in the industrial zone of the Tibú field, belonging to the Catatumbo Orinoquia operations management of Ecopetrol S.A. The improvement of the working conditions of electrical maintenance technicians is sought, so that they can carry out their maintenance activities and equipment tests in an ideal manner, with respect to the intervention required by each one of them, achieving that the useful life of the company assets more durable. This implementation is based on integrating the legal standards and modern components that currently apply to this type of structure, ensuring that it meets quality and safety standards, as well as its effectiveness when intervening or maintaining electrical equipment.